Retraction Note: Anti-inflammatory effect of atorvastatin on vascular reactivity and insulin resistance in fructose fed rats - Mahmoud, Mona F.; El-Nagar, Mohamed; El-Bassossy, Hany M. (Archives of pharmacal research, 2025)
Retraction To: Archives of Pharmacal Research https://doi.org/10.1007/s12272-012-0117-8 The Editor-in-Chief has retracted this article because of concerns regarding the figures presented in this work. These concerns call into question the article's overall scientific soundness. An investigation conducted after its publication discovered the following issues: The Control Panel in Fig. 8 appears to overlap, when re-scaled and rotated, with the Insulin Resistant Panel in Fig. 3 in El-Bassossy et al. (2011); The Atorvastatin Panel in Fig. 8 appears to overlap, when re-scaled and rotated, with the Control Panel in Fig. 3 in El-Bassossy et al. (2011). The panels in question represent tissues taken from animals subject to different experimental conditions. The Editor-in-Chief therefore no longer has confidence in the integrity of the research presented in this article. The authors disagree with this retraction. Reference El-Bassossy HM, El-Moselhy MA, Mahmoud MF (2011) Pentoxifylline alleviates vascular impairment in insulin resistance via TNF-α inhibition. Naunyn-Schmiedeberg’s Arch Pharmacol 384:277–285. https://doi.org/10.1007/s00210-011-0669-z Retraction To: Archives of Pharmacal Research https://doi.org/10.1007/s12272-012-0117-8 The Editor-in-Chief has retracted this article because of concerns regarding the figures presented in this work. These concerns call into question the article's overall scientific soundness. An investigation conducted after its publication discovered the following issues: The Control Panel in Fig. 8 appears to overlap, when re-scaled and rotated, with the Insulin Resistant Panel in Fig. 3 in El-Bassossy et al. (2011); The Atorvastatin Panel in Fig. 8 appears to overlap, when re-scaled and rotated, with the Control Panel in Fig. 3 in El-Bassossy et al. (2011). The panels in question represent tissues taken from animals subject to different experimental conditions. The Editor-in-Chief therefore no longer has confidence in the integrity of the research presented in this article. The authors disagree with this retraction. Reference El-Bassossy HM, El-Moselhy MA, Mahmoud MF (2011) Pentoxifylline alleviates vascular impairment in insulin resistance via TNF-α inhibition. Naunyn-Schmiedeberg’s Arch Pharmacol 384:277–285. https://doi.org/10.1007/s00210-011-0669-z KCI Citation Count: 0